PERANCANGAN SISTEM TANGGAP DARURAT MENGGUNAKAN FRAMEWORK TOGAF - Sintaria Br. Sembiring (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2018)
The most frequent problem of emergency response is the delay in providing assistance to refugees, some of the factors why this delay is common: It must go through some bureaucratic procedures, the differentiation of disaster areas, and the delays in Information that reach the government. Badan penangulangan bencana daerah (BPBD) responsible for handling emergency response. To carry out its functions, BPBD needs to be equipped with an information system that suits the organization '5 business strategy and can help BPBD achieve its business objectives. This study aims to make the information system architecture planning, and produce blueprint development of information systems at the emergency response stage.